Josefina Plá and the clay as a place of archive. - Cota, Débora (2018)
The clay in Josefina Plá (Spain, 1903 - Paraguay, 1999) presents a grandiose and unfinished archive on the cultural history of Paraguay and in its interior shows an effective concern with the Paraguayan cultural identity, as well as the appreciation of the figure of the Other claiming it as forming element of such culture. This work, therefore, is dedicated to the archive policies adopted by her about the clay, especially to what is meant by a " memory desire " and a "identity desire " linked to the construction of the history of Paraguay. It starts, especially, from the analysis of the tale “La mano en la tierra” and the author's study on pottery, titled La cerámica popular paraguaya (1994). But, it is also considered its ceramic production and its study on the Spanish-Guarani clay. In these works, clay is a productive element and presents itself as a place of archive (DERRIDA) where Paraguay is printed, inscribed, consigned and produced. Josefina Plá arrives in Paraguay in 1926 and gets involved with the country's assumed culture, in many cases the role of propellant, systematizer and conveyor the Paraguayan culture. In addition to being an artist and writer, she constantly participates in the discussion, debates and research, developing the important task of archivist of that culture.